KAJIAN TEORITIS TERHADAP PENGGUNAAN HAK KHIYAR PADA AKAD MURABAHAH DI BANK SYARIAH - Khairiah Elwardah (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2019)
The purpose of this study is to describe about the implementation of khiyar’s right on murabahah aqad in sharia bank theoritically. Type of research is library research